Exploring the advantages, challenges and strategies of online medical education during the COVID-19 pandemic: A Structured Narrative Review - Zhang, Yang; Pang, Guoliang; Liang, Men; Zhan, Shuyu; Li, Xiaoming (Journal of the Pakistan Medical Association, 2026)
In late 2019, the coronavirus disease-2019 pandemic emerged in Wuhan, China, and rapidly spread across the globe. Many medical schools and institutions implemented online medical education to mitigate the spread of the virus. The current narrative review was planned to provide to explore how the pandemic affected the medical education sector and the transition to online teaching. The review synthesised empirical research on online medical education since the pandemic through thematic content analysis, comprehensively analysing 33 high-quality published studies involving students and teachers from medical colleges in various countries, their attitudes and satisfaction towards online medical education, and the pros and cons of such a mode of education. Moreover, it’s the effects of online education on students' learning, personal lives and career development were explored. Finally, the review aimed at offering practical solutions to address the challenges facing online medical education. The review would likely attract further attention to online medical education, promoting awareness and supporting its future development and progress. Future research could focus on developing an efficient blended teaching model that combines online and in-person teaching, establishing a reasonable proportion of integrated teaching time. Key Words: COVID-19, Online education, Medical education, Online medical education, Structured narrative review.